2017
DOI: 10.1177/2059700217733916
|View full text |Cite
|
Sign up to set email alerts
|

Concussion in motor sport: A medical literature review and engineering perspective

Abstract: WARNING: motor sport can be dangerous'. The spectrum of head injuries in motor sport has shifted dramatically in recent decades, fuelled by advances in medicine and engineering. Despite these successes, there are growing public and professional concerns regarding concussion in motor sport. This review appraises the published literature concerning concussion in motor sport, with particular focus on the current medical and technical challenges in the field. The incidence and assessment of concussion in motor spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…However, published evidence of the experiences, knowledge and attitudes of key motorsport stakeholders (e.g., medical personnel, drivers) is lacking, and there is a significant knowledge gap regarding concussion in motorsport specifically 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, published evidence of the experiences, knowledge and attitudes of key motorsport stakeholders (e.g., medical personnel, drivers) is lacking, and there is a significant knowledge gap regarding concussion in motorsport specifically 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Motorsport has more than 80 million people involved worldwide 6 and an increasing number of younger participants entering the sport 5 . The exact number of drivers is unknown, because unlicensed drivers may be three times the number of licensed at any one time 7 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the incidence of motorsport concussion in the literature varies from 6.3 to 25%. These studies are difficult to compare, ranging from local to national events, lasting from 1 day to over a decade and including tens, or tens of thousands of individuals [ 5 ]. In addition, competition-specific figures are scarce but are most well defined for motocross, where concussion is highlighted as one of the most common injuries sustained, with presentations ranging from 9.5 to 29%.…”
Section: Concussion In Motorsportmentioning
confidence: 99%
“…8 What little there is suggests that even though there has been significant investment in safety, drivers continue to experience a greater risk of concussion compared with other high-risk sports. 9 Furthermore, a recent survey in the international journal of motorsport medicine, AUTO+Medical , found that 70% of competitors: ‘did not feel completely normal’ when they attempted to return-to-race following concussion. 10 This landscape in the motorsport environment specifically—a relatively high concussion incidence combined with competitors returning before they have fully recovered—may leave competitors in control of a high-speed vehicle that poses an ongoing threat to the individual, other participants, and the public.…”
Section: Introductionmentioning
confidence: 99%
“…A baseline assessment is advised, so that post-injury outputs can be directly compared with an individual’s previous results. Although ImPACT has been used at varying levels of motorsport competition worldwide since the early 2000's, to date there has been no formal validation of its use for four-wheeled motorsport competitors specifically, 9 with only a single published study in motocross which does not include post-injury data. 12 In motorsport therefore, as in other high-risk sports, there is a growing need for an objective, rapid and accurate diagnostic tool for concussion, validated with sport-specific data.…”
Section: Introductionmentioning
confidence: 99%